Mixture Formation Analysis for Diesel, n-Dodecane, RME, and HVO in Large-Scale Injector Nozzles - Fajri, Hamidreza; Clemente Mallada, Rafael; Rieß, Sebastian; Strauß, Lukas; Wensing, Michael (CO2 Reduction for Transportation Systems Conference, 2022)
Momentum conservation is a principle rule that affects the behaviour of vapour jet and liquid spray penetration. The air entrainment and mixture formation processes are dominated by the momentum transferred from the fuel to the ambient gas. Thus, it is a significant factor in the development of spray and jet penetration. This mixture formation process is well described for small-scale passenger car injectors; however, it has to be investigated in more detail for large-scale injector nozzles. The current work provides qualitative and quantitative results of spray and jet parameters in a constant volume combustion chamber (CVC). Two optical methods have been utilized to evaluate spray and jet details: Schlieren photography as a method to visualize the jet penetration and cone angle as well as Mie scattering for the phase change evaluation and the determination of liquid spray parameters. The temperature and pressure of inert gas and fuel inside a CVC are set to exemplify engine conditions. The chamber temperature is ranged between 873 to 973K, the chamber pressure is increased from 5 to 7 MPa and the injection pressure is changed between 50 to 150 MPa. Four fuels are selected in order to shed light upon the effects of fuel properties on spray and jet parameters. As a part of this evaluation, n-dodecane and two types of bio-diesel fuel generations, RME (1st Generation) and HVO (2nd Generation) are dissected to expand their influences on mixture formation, which can be connected to the emission production in diesel engines. Finally, two large-scale injector nozzles with an outlet hole diameter of 300 μm (cylindrical and conical nozzles) cover the effects of geometry parameters on spray and jet development. The results accentuate the fact that the liquid spray parameters are effectively fuel-dependent, while total jet parameters are mostly affected by nozzle geometry. Liquid spray length is varied from n-dodecane as a low-boiling fuel to RME as a less-volatile fuel. The conical nozzle results in less cavitation, which is effectively influential on liquid spray and total jet penetration
Keywords: ICE; Large Scale Nozzel; Fuel; Mixture Formation